Analisis Faktor Kepatuhan Obat ARV Saat Pandemi Covid-19 di Yayasan Cakap Peduli AIDS Turen - Tri Nurhudi Sasono (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2021)
HIV / AIDS is a disease caused by the Human Immunodeficiency Virus which lowers immunity by infecting and damaging the human immune system. Adherence to taking medication can increase the expectation and quality of life of PLWHA. The health condition of PLWHA is influenced by adherence to taking medication. The purpose of this study was to analyze the factors that influence medication adherence to people living with HIV / AIDS (PLWHA). The design of this research is analytic observational with aapproach cross sectional. The sample usedtechnique purposive sampling at NGO CAKAP AIDS Turen as many as 60 respondents. Retrieval of data using-based questionnaires. The statistical test is using multiple linear regression analysis. The results show that there is an influence of knowledge with a p-value of 0.017 <0.05 with a coefficient of 0.309, there is no influence on motivation with a p-value of 0.109> 0.05 with a coefficient of 0.107 and there is the effect of access to health services with a p-value of 0.012 <0.05 with a coefficient of 0.406. Based on these statistical results, it can be concluded that the factors that influence medication adherence are knowledge and access to health services.